2014
DOI: 10.1016/j.aca.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical assessment of water|ionic liquid biphasic systems towards cesium extraction from nuclear waste

Abstract: A room temperature ionic liquid (IL) composed of a quaternary alkylphosphonium (trihexyltetradecylphosphonium, P66614(+)) and tetrakis(pentafluorophenyl)borate anion (TB(-)) was employed within a water|P66614TB (w|P66614TB or w|IL) biphasic system to evaluate cesium ion extraction in comparison to that with a traditional water|organic solvent (w|o) combination. (137)Cs is a major contributor to the radioactivity of spent nuclear fuel as it leaves the reactor, and its extraction efficiency is therefore of consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…In particular, in the field of metal extraction/separation/recycling by liquid/liquid processes, hydrophobic ILs of the type [C n C m im][Tf 2 N] (1-alkyl, 3-alkyl-imidazolium bis(trifluoromethylsulfonyl)imide) have already proved to be tremendously efficient media for a large variety of metals, [9] from Li + to Pu 4 + , [10,11] including d-elementATT="tptxpt=0mm tptxt=5mm tptxb=1.4mm"s [1,2,[11][12][13] and lanthanoids. [14][15][16][17][18][19] The huge potential that ILs present for extraction processes results from the complex extraction mechanisms, which are strongly dependent not only on the nature of the IL but also on the aqueous phase composition, [20] most often based on nitric or hydrochloAqueous-ionic liquid (A-IL) biphasic systems have been examined in terms of deuterated water, acid, and IL cation and anion mutual solubilities in the upper (water-rich, in mole fraction) and lower phase of aqueous/IL biphasic systems at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the field of metal extraction/separation/recycling by liquid/liquid processes, hydrophobic ILs of the type [C n C m im][Tf 2 N] (1-alkyl, 3-alkyl-imidazolium bis(trifluoromethylsulfonyl)imide) have already proved to be tremendously efficient media for a large variety of metals, [9] from Li + to Pu 4 + , [10,11] including d-elementATT="tptxpt=0mm tptxt=5mm tptxb=1.4mm"s [1,2,[11][12][13] and lanthanoids. [14][15][16][17][18][19] The huge potential that ILs present for extraction processes results from the complex extraction mechanisms, which are strongly dependent not only on the nature of the IL but also on the aqueous phase composition, [20] most often based on nitric or hydrochloAqueous-ionic liquid (A-IL) biphasic systems have been examined in terms of deuterated water, acid, and IL cation and anion mutual solubilities in the upper (water-rich, in mole fraction) and lower phase of aqueous/IL biphasic systems at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…ILs have been used in a wide variety of applications including battery electrolytes [4][5][6], solvent for nanoparticle synthesis [7], as antibacterial agents [8], etc. It has been shown that hydrophobic ILs are good candidates for metal ion extraction in biphasic, water|IL (w|IL) [9][10][11][12], systems. In metal ion extraction, a hydrophobic ligand is typically dissolved in the organic phase and coordinates with the metal ion either interfacially or in the bulk organic/aqeuous phase [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In metal ion extraction, a hydrophobic ligand is typically dissolved in the organic phase and coordinates with the metal ion either interfacially or in the bulk organic/aqeuous phase [13,14]. Conventional means of separation have been through physical mixing of the two phases [9,15]; however, as previously demonstrated [10][11][12]16], this process can also be investigated electrochemically using liquid|liquid electrochemistry performed at a polarizable interface between two immiscible electrolytic solutions (ITIES) [13,14,[17][18][19][20][21]. Furthermore, in order to reduce samples sizes and improve sensitivity, a micro-ITIES is often employed, such as at the tip of a pulled borosilicate glass capillary [11,16,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The use of pipet electrodes based on ionic transfer across an interface between two immiscible electrolyte solutions (ITIES) 2841 has been an important method to detect ionic analytes. Ionic transfer of neurotransmitters across ITIES, mainly micro- and macrointerfaces has been reported.…”
mentioning
confidence: 99%